2022
DOI: 10.1037/abn0000723
|View full text |Cite
|
Sign up to set email alerts
|

Young children with suicidal thoughts and behaviors more likely to resolve conflicts with violence, homicide, or suicide: A study of internal working models using narratives.

Abstract: There is mounting evidence that young children who express suicidal ideation (SI) have a different conceptualization of death than their peers. This study characterizes 3-to 6-year-olds' depictions of violence, death, and suicidal themes in a story completion task as a function of their history of SI. Participants were 228 children with depression (3.0-6.9 years) who completed a comprehensive psychiatric assessment and four story stem narratives. For each narrative, an interviewer began a story with a conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…However, these findings were exploratory and additional confirmatory research will be necessary to replicate these findings. If confirmed, these findings could add to the growing literature documenting the correlates of early childhood suicidal thoughts and behaviors including: child and family psychopathology (Whalen et al, 2015), greater exposure to violent life events (Luby et al, 2019), an enhanced understanding of death (Hennefield et al, 2019), and greater reliance on violence (including suicide) to resolve conflicts (Hennefield et al, 2022). Adding early sleep difficulties to this set of correlates enhances the clinical picture of young children who experience suicidal thoughts and behaviors, and may offer a feasible target for direct, early intervention.…”
Section: Discussionmentioning
confidence: 64%
“…However, these findings were exploratory and additional confirmatory research will be necessary to replicate these findings. If confirmed, these findings could add to the growing literature documenting the correlates of early childhood suicidal thoughts and behaviors including: child and family psychopathology (Whalen et al, 2015), greater exposure to violent life events (Luby et al, 2019), an enhanced understanding of death (Hennefield et al, 2019), and greater reliance on violence (including suicide) to resolve conflicts (Hennefield et al, 2022). Adding early sleep difficulties to this set of correlates enhances the clinical picture of young children who experience suicidal thoughts and behaviors, and may offer a feasible target for direct, early intervention.…”
Section: Discussionmentioning
confidence: 64%
“…A further strength of this study is that we relied on child‐reported SITBs, as research has demonstrated high discordance between child‐reported and parent‐reported SI/SB in the ABCD dataset, with a lack of parent agreement being observed in more than 75% of children reporting SI/SB (DeVille et al, 2020). This suggests that the majority of caregivers of suicidal children are unaware of (or do not report) information regarding their child's suicidality, underscoring the value of asking children directly about SITBs, especially given that evidence suggests that children can reliably report SITBs (e.g., Hennefield et al, 2022; Luby et al, 2019; Whalen et al, 2015). Regarding limitations, despite the question “Are you transgender?” being face‐valid, a noteworthy number of participants reported not understanding the question (39.5%) who were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐injurious thoughts and behaviors are present among children as early as the preschool period of development (e.g., Hennefield et al, 2022; Luby et al, 2019; Whalen et al, 2015). Although one may assume that children this age do not understand what it means to die, prior work has demonstrated that depressed young children presenting with SI/SB have a better understanding of death than their non‐suicidal peers (Hennefield et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosenthal and Rosenthal (1984) examined 16 suicidal preschoolers (2.5–5 years old) referred to a child psychiatry outpatient clinic after attempting to seriously injure themselves and found that they had significantly more non‐suicidal self‐directed aggression, loss of interest, morbid ideas, depression, impulsivity and hyperactivity, and running‐away behavior than behaviorally disordered preschoolers. Finally, data suggest that young children with active SI are more likely than their depressed peers without SI to incorporate violence, homicide, and suicide into their narratives around conflict resolution (Hennefield et al, 2022).…”
Section: Introductionmentioning
confidence: 99%